IMPLEMENTASI RADIUS SERVER PADA JARINGAN VIRTUAL PRIVATE NETWORK - Pramana, ivan Joi; Widyastuti, Naniek; Triyono, Joko (Jurnal Jarkom, 2014)
ABSTRACTVPN network architecture is motivated by the needs of the existence of a network that specializes certain users to access personal data from a server. Virtual Private Network ( VPN ) is a network of local communication system over a public network . While RADIUS is a networking protocol that is used as the authentication and recording of user accounts connected VPN network , VPN Implementation Radius network is useful to establish a system of local network through a public network where the user account can be set and in monitoring by using web authentication . The data will pass through the VPN network traffic is encapsulated by the underlying network . In VPN networks , the Internet is a medium that is becoming mainstream in the communication process . That is because the Internet becomes an access point to transfer data between different client location or the location of the VPN server . VPN network on the test results it can be seen that the VPN data traffic can provide a solution to transfer data with a diversity of sizes and file types . The process of data transfer in a VPN network can use FTP , SFTP , SMB . Differences between the client location becomes a its own advantages in using a VPN network that is useful for exchanging data or resources.Keywords: VPN, RADIUS,network